Comparative Assessment of Deferiprone and Deferasirox in Thalassemia Major Patients in the First Two Decades-Single Centre Experience. (14th February 2013) - Zachariah, Mathew; Tony, Surekha; Bashir, Wafa; Al Rawas, Abdulhakim; Wali, Yasser; Pathare, Anil
<x xml:space="preserve">Abstract</x> Iron overload is mainly responsible for the morbidity and mortality in patients with beta thalassemia major (TM). Our aim was to compare treatment outcomes with oral iron chelators, deferiprone (DFP), and deferasirox (DFX) in the first two decades on therapy. Seventy patients with TM (mean age ± SD, 7.9 ± 4.2; range 1.5–17 years) attending the pediatric day care unit for regular transfusional support were enrolled in this cross-sectional cohort study. The patients were treated either with DFP at the dose of 75–100 mg/kg/d in three divided doses after food or DFX at the dose of 25–40 mg/kg/d as single dose before food. Mean serum ferritin (±SD) was lower in patients below 10 years (n = 44) at 1283 (±600) ng/mL when compared with patients ≥10 years (n = 19) at 1546 (±589) ng/mL. There was no significant difference in mean serum ferritin (±SD) level in patients receiving DFP (1360 ± 589) versus DFX (1260 ± 641) in this cohort, P > 0.05. 67% of the patients had Vitamin D deficiency (<50 umol/L). Our results show comparable efficacy of DFP and DFX with regards to iron chelation as estimated by serial serum ferritin levels; however, MRI T2* values were higher in the DFP-treated patients compared to DFX treatment.